Sustratos para semilleros tecnificados. Estudio en canteros - Guzman, P.=700 1 Rodriguez, L.; Baños, C.
(Es, En)
Ilus., 13 ref.
Keywords: NICOTIANA TABACUM; SUBSTRATOS DE CULTIVO; SEMILLERO; TECNOLOGIA; CUBA